Hubungan Tingkat Kecemasan Peserta Didik dengan Hasil Uji Kompetensi Keahliahn Jurusan TBSM di SMK N 1 Pleret - Lestari, Puji Eka; Budiyono , Nararya Rahadyan (CV. Generasi Insan Rafflesia, 2024)
Implementation of the Skills Competency Test (UKK) is an assessment carried out specifically for students at SMK which aims to measure the achievement of students' competencies and skills. This research aims to 1) determine the anxiety level of students who take the Skills Competency Test (UKK); 2) Find out whether there is a relationship between anxiety levels and the results of the Skills Competency Test (UKK). The research method used is correlational research with a quantitative approach. The instrument used was a questionnaire measuring anxiety, the Zhung Self-Rating Scale (ZSAS), which was then modified according to the needs of the researcher. The respondents in this study were 67 students who were sampled using a saturated sampling technique. The data analysis method used is the Pearson Product Moment correlation technique. The results of the research were that 44 respondents had a normal/not anxious level of anxiety, 20 respondents had a mild level of anxiety, and 3 respondents had a moderate level of anxiety. Another research result, namely from the calculation of the product moment correlation test, was obtained a tcount value of (-0.077) < ttable (1.671), which means there is no relationship between the level of anxiety and the results of the Skills Competency Test (UKK) in the TBSM department at SMK N 1 Pleret. The benefits of this research are, 1). Can make it easier for teachers to provide direction and services that are appropriate to students' anxiety levels, 2). Teachers can find out the factors that cause anxiety in students so they can provide guidance and counseling services that are tailored to students' needs. The limitation of this research is that the number of respondents is relatively small. Apart from that, the researcher only conducted research on two variables, namely the level of anxiety and the results of the Skills Competency Test (UKK). Suggestions for future researchers include developing research variables such as the influence of anxiety on learning outcomes, developing innovations and strategies for overcoming anxiety as well as action research that can help overcome student anxiety.